Jumping-based asymmetries are negatively associated with jump, change of direction, and repeated sprint performance, but not linear speed, in adolescent handball athletes - Madruga-Parera, M.; Bishop, C.; Read, P.; Lake, J.; Brazier, J.; Romero-Rodriguez, D. (Journal of Human Kinetics, 2020)
The aim of the present study was to determine the association of multi-directional jumping asymmetries with measures of physical performance. Forty-two youth handball athletes (age: 16.0 ± 1.3 years; body height: 174.11 ± 7.3 cm; body mass: 70.49 ± 13.3 kg) performed a mid-season fitness test battery consisting of single leg countermovement, lateral and broad jump tests, two change of direction speed (CODS) tests, an 8 x 10 m repeated sprint test, and a 20 m sprint. The Kappa coefficient showed only `slight` levels of agreement (K range = -0.05 to 0.15), indicating that asymmetries rarely favoured the same side during each of the jump tests. The single leg countermovement jump showed significantly (p = 0.006) larger asymmetries (11.2 ± 8.4) than the broad jump (6.4 ± 4.6) and significant correlations were present between jumping asymmetries and jump (r = -0.32 to -0.52), CODS (r = 0.31 to 0.32) and repeated sprint (r = 0.35 to 0.40) performance. The findings of the present study highlight the independent nature of jumping asymmetries and associations with measures of physical performance. Practitioners are encouraged to use multiple tests to detect existing side differences and consider appropriate training interventions for the reduction of inter-limb asymmetries.